The Effect of Islamic Marketing Mix towards Costumer Loyalty and Customer Satisfaction on Shopee Millennial Muslim - Moch Syafi'i; Mohamad Mondir; M. Zikwan; Zainul Anwar (ITB AAS INDONESIA Surakarta, 2023)
The improvement of internet creates many e-commerce in Indonesia. E-commerce became a receptacle for millennial generation who want to buy goods and services online. In Indonesia, Shopee is e-commerce that has become market leader. Shopee is using Islamic marketing mix to maintain its position in Indonesian market. The purpose from this research is to analyze the influence of Islamic marketing mix (product, price, place, promotion, process, people and physical evidence) on customer loyalty towards customer satisfaction. This research is quantitative research. The sampling technique used is random sampling and convenience sampling. Skala Likert will be used for measuring the data collected. There are 159 samples from millennial Muslims in Jember for this research. The data that has been collected will be analyzed using path analysis. The result indicated that product, place, promotion, and people significantly affect customer satisfaction while price, process, and physical evidence are not significant. Product, promotion, and physical evidence also have substantial effects on customer loyalty while price, place, process, and people are not. Customer satisfaction also has no significant effect on customer loyalty. The result also shows that customers cannot mediate product, price, place, promotion, process, people, and physical evidence towards customer loyalty.